Development of hymenaea courbaril l. Var. Stilbocarpa seedlings in different fertilizers and substrate composition - Pagliarini, Maximiliano Kawahata; Castilho, Regina Maria Monteiro de; Moreira, Erica Rodrigues; Mariano-Nasser, Flávia Aparecida de Carvalho; Alves, Marlene Cristina (Agrarian, 2019)
The objective was to test the development of Hymenaea courbaril seedlings in different substrates and different fertilizers. The experiment was conducted at São Paulo State University (UNESP), School of Engineering, Ilha Solteira, Brazil in greenhouse Pad & Fan type. Seedlings were grown in same environment and 20 days after sowing they were transplanted into seedlings black bags (5 litres of volume) with following substrates: S1 = soil + organic compound (1:1) and S2 = soil + cellulose residue (1:1). Fertilizer treatments were: T1 = Control, T2 = Osmocote® (15-09-12), T3 = Osmocote® (14-14-14), T4 = conventional fertilizer (04-30-10). The evaluated traits were: plant height (cm), diameter of plants stems (mm), leaves chlorophyll content (mg 100 cm-2) and dry weight of root and shoot (g). The experimental design was completely randomized in factorial scheme 4 x 2 (substrates x fertilizer) totalling eight treatments and 13 repetitions, one plant per plot. According to all evaluated traits, the most indicated substrate for Hymenaea courbaril seedlings development was soil + organic compound using Osmocote® (15-09-12) as fertilizer.